Protection system against overload and distributed denial of service attacks. (22nd February 2010) - Toth, Ervin; Hornak, Zoltan; Toth, Gergely
Detection of overload and protection from denial of service attacks is a common problem in information system servers. Such situation may be the result of simple overload, such as increased service request rate during peak hours, or a malicious distributed attack originating from many computers. This article describes a solution to this problem, focusing on protection mechanisms against both natural and malicious overload, based on analysing the queue of requests – which, as described in this paper, is chosen to be unlimited. Furthermore, detection and protection scheme against blocking and crash-bug exploiting attacks is presented.